Biodiversity of Lithophytes in Southern Western Ghats of Palaghat, Kerala, India - Muthulakshmipechiammal, P.; Rajendran, A. (Indian Forester, 2020)
The present paper focuses on biodiversity of lithophytic plant species of Kozhinjampara situated in Southern Western Ghats of Palghat district, Kerala. A total number of 102 lithophytic species in 76 genera and 41 families were documented. The family Apocynaceae was most common followed by Amaranthaceae and Fabaceae. Among them epilithic habitats species is more dominant compared to cryptoendolithic, chasmoendolithic and hypolithic. Due to the fact that lithophytes are thrive in harsh environmental conditions which threaten their population. The present study may provide a baseline data for researchers to address the impact of climatic change in near future.